REVIEWS - Black, Jermy (Journal of Semitic studies, 2003)
Hammurabi's Laws. Text, translation and glossary M.E.J.Richardson . Sheffield Academic Press, Sheffield , 2000. Pp. 423 Price: £56.00 . ISBN: 1-84127-030-X.